If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5/6x+4=-1
We move all terms to the left:
5/6x+4-(-1)=0
Domain of the equation: 6x!=0We add all the numbers together, and all the variables
x!=0/6
x!=0
x∈R
5/6x+5=0
We multiply all the terms by the denominator
5*6x+5=0
Wy multiply elements
30x+5=0
We move all terms containing x to the left, all other terms to the right
30x=-5
x=-5/30
x=-1/6
| –1=h–1+ 2 | | T=225+9x | | 1=4w−11 | | 12x+3-9x=18 | | 2z-8=2z-8 | | 6w+3-2w+7=26 | | (1)/(5)x-4=(1)/(10)x | | 11×-5-x+6=2x+17 | | X(0.25)+8y=15 | | -119=17x | | 42=7x+1210x | | x/3=13+3 | | h²+3h-10=0 | | -7+5x-2=15 | | =2x+9.74 | | 8t-12=5t-7 | | 3x÷4+6=18 | | 6x=3=2x+13 | | D=(6/150)x500 | | D=6/150x500 | | 4x=511 | | 0.75x20=x | | y+0.5y=12.75 | | -3=-z/3 | | -3=-b/2 | | r+1/5=3/5 | | 80-y=155 | | -4=-v/2 | | r+1/5=2/5 | | 8=-j+5 | | x²+x=1980 | | x²+x-1980=0 |